2017
DOI: 10.1902/jop.2017.170101
|View full text |Cite
|
Sign up to set email alerts
|

Local Injection of Hyaluronic Acid Filler Improves Open Gingival Embrasure: Validation Through a Rat Model

Abstract: Open gingival embrasure was reproduced reliably in vivo. Local injection of HA filler was validated as a meaningful minimally invasive procedure to improve open gingival embrasure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
2
13
0
1
Order By: Relevance
“…An alternative method for assessing the biological response and safety of an implanted material is an implantation in the dorsal subcutaneous tissue of mice, rats, guinea-pigs, or rabbits (Pi et al, 2017 ). For example, the implantation of films made of HA tested by subcutaneous implantation into the backs of Wistar rats (Liu et al, 2005 ).…”
Section: In Vivo Tests Of Ha-based Materialsmentioning
confidence: 99%
“…An alternative method for assessing the biological response and safety of an implanted material is an implantation in the dorsal subcutaneous tissue of mice, rats, guinea-pigs, or rabbits (Pi et al, 2017 ). For example, the implantation of films made of HA tested by subcutaneous implantation into the backs of Wistar rats (Liu et al, 2005 ).…”
Section: In Vivo Tests Of Ha-based Materialsmentioning
confidence: 99%
“…3 Hyaluronic acid filler has been shown to be able to fill open gingival embrasures in an in vivo model. 6 Most previous studies have not taken the complex implications of tooth movement into consideration when evaluating open gingival embrasures. Recent studies have reported that the movement of teeth during orthodontic treatment could also affect the occurrence of open gingival embrasures.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study successfully developed an experimentally induced OGE model using rats and demonstrated the effect of HA filler injection on IDP reconstruction. However, the study also suggested the need for a histological evaluation to examine the side effects of HA filler injection [34]. Based on the findings of a previous study, OGE was mimicked by inducing IDP loss between both incisors of mice in this study [34].…”
Section: Discussionmentioning
confidence: 78%
“…However, the study also suggested the need for a histological evaluation to examine the side effects of HA filler injection [34]. Based on the findings of a previous study, OGE was mimicked by inducing IDP loss between both incisors of mice in this study [34]. The morphological changes in IDP of the OGE mouse model were evaluated after wire attachment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation